Academician Nikolay Nikolaevich Blokhin (1912–1993) (on the 110th anniversary of his birth) - A. A. Kurygin; V. S. Dovganyuk; V. V. Semenov (Вестник хирургии имени И.И. Грекова)
Professor Nikolay Nikolaevich Blokhin was born on April 21 (May 4), 1912 in the county town of Lukoyanov, Nizhny Novgorod province in the family of a doctor. After graduating from high school in 1929, Nikolay Nikolaevich entered the medical Faculty of Nizhny Novgorod University. In June 1934, N. N. Blokhin graduated with honors from the surgical department and received a diploma from the Gorky Medical Institute. For excellent studies and great abilities for research work, Nikolay Nikolaevich was enrolled in a postgraduate course at the Department of Hospital Surgery. After medical practice, N. N. Blokhin returned to the hospital surgery clinic, continued his research and operated a lot. At the beginning of the Great Patriotic War, a front-line evacuation hospital for a thousand beds № 2816 was deployed in Gorky, Nikolai Nikolaevich was appointed the leading surgeon. In 1947, N. N. Blokhin was appointed deputy director of the Gorky Research Institute of Reconstructive Surgery, Traumatology and Orthopedics for the scientific part, and in March 1948 – director of this Institute. In December 1948, Nikolai Nikolaevich was awarded the academic title of professor. On January 29, 1960, N. N. Blokhin was elected a full member of the USSR Academy of Medical Sciences, and in the evening of the same day, the Minister of Health of the USSR S. V. Kurashov proposed to elect Nikolai Nikolaevich as the president of the Academy. In 1977, the Cancer Research Center of the USSR Academy of Medical Sciences was renamed the All-Union Cancer Research Center of the USSR Academy of Medical Sciences, and N. N. Blokhin was appointed its general director. More than 100 doctoral and PhD theses were defended under his leadership. Many of his students became prominent oncologists in Russia and neighboring countries. The multifaceted, bright and fruitful activity of Nikolai Nikolaevich was repeatedly awarded with high awards of the Soviet Union. On May 16, 1993, Academician Nikolai Nikolaevich Blokhin died and was buried at the Novodevichy Cemetery in Moscow. In the same year, the name of N. N. Blokhin was assigned to the Russian Cancer Research Center of the Russian Academy of Medical Sciences.